Istota i przejaw kompetencji relacyjnej - Czakon, Wojciech (Relational Capability: Nature and Symptoms, 2008)
The author tackles the issue of relational capability nature from two standpoints: extant literature on core competencies and dynamic capabilities. It suggests that the relational capability is composed of capabilities, resources and processes dedicated to co-operation with partners. There is a need for farther research to verify six proposed relationships and ties between them to work out an operational construct of the relational capability.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 58-65